Determinants of COVID-19 immunisation uptake in a country with high mortality and a low vaccination rate - Dunja Aksentijevic; Rachel Tanner; Lejla Lazović-Pita; Almir Peštek; Ademir Abdić (Elsevier, 2023)
Background: Research concerned with attitudes towards COVID-19 vaccination in upper middle-income countries such as Bosnia and Herzegovina (B&H) is scarce. Currently, B&H has the lowest number of fully vaccinated adults in Europe, and the highest cumulative number of COVID-19 deaths and SARS-CoV-2 infected individuals. The aim of our study was to examine the factors associated with COVID-19 vaccination status in B&H. Methods: An online survey among 1304 B&H adults was conducted in October 2021 evaluating vaccine acceptance, together with socio-demographic variables, attitudes and beliefs related to COVID-19 vaccination. Results: The results from a binary logistic regression indicate that those who believed that the COVID-19 vaccine was effective were 45 times more likely to be vaccinated compared to those who did not. We also show that those who had received childhood immunisations were 41 times more likely to be vaccinated against COVID-19 compared to those who had never been previously immunised. Other significant factors were related to respondents' trust in government institutions and healthcare policymakers as well as trust in public healthcare workers. Conclusion: We suggest that future vaccination campaigns should be aimed at educating the public regarding the importance and safety of vaccines, together with strengthening trust in the public health system.